PJMHS 2021
DOI: 10.53350/pjmhs211561885
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Urinary Tract Infection in Children with Diarrhea

Abstract: Aim: To determine the frequency of UTI in children presented with diarrhea. Study Design: Cross-sectional Place and Duration: Pediatrics department of Alkhidmat Hospital, Peshawar and Sharif Medical and Dental College, Lahore for six months duration from October 2020 to March 2021. Methodology: Total 120 patients of both gender with ages 2 months to 5 years were enrolled in this study. After taking written consent from parents/guardians, detailed demographics including age, sex, residence, severity and complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…Et al. 2016 [21] , Hosseini H 2011 [22] and Aghadoost D 2012 [23] . They revealed that Home was the most frequent site of eye damage.…”
Section: Discussionmentioning
confidence: 99%
“…Et al. 2016 [21] , Hosseini H 2011 [22] and Aghadoost D 2012 [23] . They revealed that Home was the most frequent site of eye damage.…”
Section: Discussionmentioning
confidence: 99%